Estudo de modelos de dois fluidos acoplados ao método FCT em escoamentos bifásicos - Freitas, Raphael Viggiano Neves de (2017)
Numerical simulation of two-phase flows is a tool of great importance to various areas of industry, especially in the oil and gas industry, in predicting the behavior of the flows according to the main parameters of the problem. This work aims to study two different two-phase flow models, named 4E1P (four equations and single pressure) and 5E2P (five equations and two pressures), with the objective of evaluating their abilities to adequately describe some standard problems. Both models are formulated by the onedimensional mass and momentum conservation equations, and are applied to simulate two-phase flows. The models differ mainly in their eigenstructure and how the pressure is treated. The 4E1P model considers a single pressure for both phases and is conditionally hyperbolic, while the 5E2P model is unconditionally hyperbolic and considers two pressures a priori. The numerical method used to solve the partial differential equations that define the models is the FCT (Flux-Corrected Transport). First some conceptual cases that are widely covered in the literature are studied, as a way of validating and analyzing the mathematical models and the numerical method. Finally, the cases of engineering interest of stratified flows in pipelines are simulated and the results are compared with the output of a commercial software and those obtained by in the literature, showing good agreement.Também disponível on-line.